2019
DOI: 10.1016/j.ajem.2018.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient PM2.5 and emergency department visits for psychiatric emergency diseases

Abstract: a b s t r a c tBackground: Whether or not short-term exposure to particulate matter b2.5 μm in diameter (PM 2.5 ) increases the risk of psychiatric emergency diseases is unclear. Methods: The study was performed in a metropolis from January 2015 to December 2016. The exposure was PM 2.5 , and the confounders were weather (temperature and humidity) and other pollutants (PM 10 , SO 2 , CO, O 3 , and NO 2 ). The outcomes were emergency department (ED) visits with psychiatric disease codes (F00-F99 in ICD10 codes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Contrary to our hypothesis, we did not find a positive association between most of the air pollutants considered in our study, such as PM 10 , PM 2.5 , CO and NO 2 . This is in contrast with previous literature on this subject (Szyszkowicz et al ., 2009 , 2010 , 2018 ; Mehta et al ., 2015 ; Power et al ., 2015 ; Chen et al ., 2018 ; Duan et al ., 2018 ; Eguchi et al ., 2018 ; Kim et al ., 2018 ; Oudin et al ., 2018 ; Shin et al ., 2018 ; Song et al ., 2018 ; Bai et al ., 2019 ; Lee et al ., 2019 ; Qiu et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our hypothesis, we did not find a positive association between most of the air pollutants considered in our study, such as PM 10 , PM 2.5 , CO and NO 2 . This is in contrast with previous literature on this subject (Szyszkowicz et al ., 2009 , 2010 , 2018 ; Mehta et al ., 2015 ; Power et al ., 2015 ; Chen et al ., 2018 ; Duan et al ., 2018 ; Eguchi et al ., 2018 ; Kim et al ., 2018 ; Oudin et al ., 2018 ; Shin et al ., 2018 ; Song et al ., 2018 ; Bai et al ., 2019 ; Lee et al ., 2019 ; Qiu et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, long-term exposure to ambient air pollution could be an independent risk factor for mental health disorders ranging from subjective stress to depressive disorders and suicidal ideation (Shin et al ., 2018 ). Recent studies analysing the association between daily levels of air pollutants and hospital admissions for mental disorders showed significant results for different pollutants considered both for admissions for generic mental disorders (Chen et al ., 2018 ; Kim et al ., 2018 ; Song et al ., 2018 ; Lee et al ., 2019 ; Qiu et al ., 2019 ) and for specific diagnoses such as schizophrenia (Gao et al ., 2017 ; Duan et al ., 2018 ; Bai et al ., 2019 ), depression (Szyszkowicz et al ., 2016 ; Wang et al ., 2018 ) and substance abuse (Szyszkowicz et al ., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have reported a relationship between IEQ and sleep quality [48], musculoskeletal disorders [49], sick building syndrome [50][51][52], sensorial symptoms [53] and performance at work [54] this study demonstrated that perceived IEQ parameters, namely air quality, thermal comfort, noise and lighting in the workplace were associated with psychological distress. While air quality has long been known to impact our physical health, its effect on our mental health has only recently come to fore [55][56][57]. A recent exploratory study using a dataset with more than 150 million individuals from the US and Denmark reported a significant association between air pollution exposure and the risk of neuropsychiatric disorders [55].…”
Section: Perceived Ieq Relates To Psychological Distress In All Workpace Environmentsmentioning
confidence: 99%
“…Lastly, in terms of environmental characteristics, the association between PM 2.5 with SMI prevalence we observed in this study is consistent with previous research. Air pollutants affect the brain in several ways [4], are responsible for the activation of inflammatory processes [73], and are linked with increased hospital admissions for mental illnesses [74][75][76], so it was expected that LSOAs with high levels of PM 2.5 would report high SMI prevalence rates.…”
Section: Plos Medicinementioning
confidence: 99%